Metal free mild and selective aldehyde cyanosilylation by a neutral penta-coordinate silicon compound - Swamy, V. S. V. S. N.; Bisai, Milan Kumar; Das, Tamal; Sen, Sakya S. (Chemical Communications, 2017)
This study demonstrates the preparation and structural characterization of a Si(IV) hydride (PhC(NtBu)(2)SiH(CH3)Cl) (1) and its use as a catalyst for the cyanosilylation of a variety of aldehydes. Compound 1 represents the first neutral penta-coordinate silicon(IV) species that catalyzes cyanosilylation of aldehydes under mild conditions.

Lithium compounds as single site catalysts for hydroboration of alkenes and alkynes - Bisai, Milan Kumar; Yadav, Sandeep; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2019)
The hydroboration of alkenes and alkynes using easily accessible lithium compounds [2,6-di-tert-butyl phenolatelithium (1a) and 1,1 ` dilithioferrocene (1b)] has been achieved with good yields, high functional group tolerance and excellent chemoselectivity. Deuterium-labeling experiments confirm the cis-addition of pinacolborane. The methodology has been further extended to myrcene, which undergoes selective 4,3-hydroboration. DFT calculations provide insights into the mechanism.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Access to a variety of Ge(II) and Sn(II) compounds through substitution of hypersilyl moiety - Bisai, Milan Kumar; Ajithkumar, V. S.; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
We have prepared amidinato-germylene (3) and -stannylene (4) with a tris(trimethylsilyl)silyl substituent and subsequently substituted the hypersilyl moiety by reacting 3 with chlorophosphines, which led to phosphino germylenes (5 and 6) with concomitant liberation of (Me3Si)(3)SiCl. Exploiting the fluoride affinity of the silicon atom, we have prepared pentafluoropyridyl germylene (7) and -stannylene (8) by reacting 3 and 4 with C5F5N with simultaneous elimination of (Me3Si)(3)SiF. These are the first examples of aryl germylenes or stannylenes prepared via C-F bond activation of a perfluoroarene. The reaction of 4 with Me3NO resulted in a novel Sn2O2 ring (9). All compounds were characterized by single-crystal X-ray structure determination studies.

Deoxygenative hydroboration of primary and secondary amides: a catalyst-free and solvent-free approach - Kumar, Rohit; Bisai, Milan Kumar; Jain, Shailja; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
In contrast to the recent reports on catalytic hydroboration of amides to amines with pinacolborane (HBpin), a simple catalyst-free and solvent-free method for the hydroboration of a variety of amides has been realized. To get the mechanistic insights, DFT calculations have been performed.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Diverse reactivity of hypersilylsilylene with boranes and threecomponent reactions with aldehyde and HBpin - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2021)
The recently reported hypersilylsilylene PhC-(NtBu)(2)SiSi(SiMe3)(3) (1) reacts with BH3, 9-BBN, and PhBCl2 to yield the respective Lewis acid base adducts 2-4, respectively. Compound 4 undergoes isomerization to form a ring expansion product 5. The same silylene was found to initially form an adduct with HBpin (6) and subsequently isomerized to 7 via the rupture of the B-H bond of HBpin (7), where the hydride was bound to the carbon atom of the amidinate ligand and the Bpin unit was attached to the silicon center. Surprisingly, the reaction of 1 with HBcat results in PhC(NtBu)(2)Bcat (8). Subsequently, we have shown that HBcat forms the same product when it reacts with related silylene PhC(NtBu)(2)SiN(SiMe3)(3) (1'). With all of these reactions in hand, we ponder if silylene can activate two small molecules at one time. In this work, we delineate the three-component reactions of silylenes 1 and 1' with 4-fluorobenzaldehyde and HBpin, which afforded unusual coupling products, 9 and 10, respectively. Note that 9 and 10 were prepared from the cleavage of the B-H and C=O bonds by silylene in a single reaction and are the first structurally attested Si-C-O-B coupled products.

Lithium compound catalyzed deoxygenative hydroboration of primary, secondary and tertiary amides - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2021)
A selective and efficient route for the deoxygenative reduction of primary to tertiary amides to corresponding amines has been achieved with pinacolborane (HBpin) using simple and readily accessible 2,6-di-tert-butyl phenolate lithium center dot THF (1a) as a catalyst. Both experimental and DFT studies provide mechanistic insight.

Reactivities of silaimines with boranes: from cooperative B-H bond activation to donor stabilized silyl cation - Bisai, Milan Kumar; Sharma, Vishal; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
The recently published silylene with a tris(trimethylsilyl) group, PhC(NtBu)(2)SiSi(SiMe3)(3) (1), was reacted with the organic azides such as SiMe3N3 and AdN(3) to form the respective hypersilylsilaimines, PhC(NtBu)(2)Si(=NR)Si(SiMe3)(3) 2 (R = SiMe3) and 3 (R = Ad). The B-H bond of HBpin or HBcat was split across the Si=N bond upon reaction with 2, which generated 4 and 5, respectively. However, we could not obtain the crystals of 4 and 5 appropriate for X-ray diffraction. Subsequently, we performed the analogous reactions with a related silaimine PhC(NtBu)(2)Si(=NSiMe3)N(SiMe3) 2 (2') and isolated similar B-H bond activated products 6 and 7. The reaction of 2' with HBCl2 resulted in donor stabilized silyl cations (8 and 9) supported by an amidinate ligand.

Readily available lithium compounds as catalysts for the hydroboration of carbodiimides and esters - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Journal of Organometallic Chemistry, 2021)
Selective and efficient hydroboration of esters and carbodiimides to alcohols and amines by two welldefined and readily accessible lithium complexes, 2,6-di-tert-butyl phenolate lithium (1a ) and 1,1'-dilithioferrocene (1b ) are described. A range of aliphatic, aromatic, and cyclic esters with various functional groups were selectively converted into the corresponding boronate esters. Similarly, the single hydroboration of carbodiimides with aliphatic and aromatic substituents on the nitrogen atoms was studied. A possible mechanistic pathway of the hydroboration of carbodiimides with HBpin has been proposed using NMR studies and DFT calculations. These reactions are convenient alternatives to stoichiometric hydride reduction or hydrogenation. The employing of lithium complexes is also significant, because of the need to find cheap and green alternatives to noble metal complexes. (C) 2021 Elsevier B.V. All rights reserved.

Substrate, catalyst, and solvent: the triune nature of multitasking reagents in hydroboration and cyanosilylation - Dixit, Ruchi; Bisai, Milan Kumar; Yadav, Sandeep; Yadav, Vinita; Sen, Sakya S.; Vanka, Kumar (Organometallics, 2021)
A truly green chemical process would avoid the use of an external catalyst, while still achieving high efficiency. This has been realized in the very recent past for hydroboration, cyanosilylation, acetalization, and the aza-Michael addition, among other reactions. The current combined computational and experimental study unlocks the secret to how this highly desirable outcome is accomplished: one of the reactants in the process also acts as the catalyst. Specifically, this is shown (i) for the important hydroboration reaction, with pinacolborane (HBpin) as the hydroborating reagent and benzaldehyde, acetophenone, benzoic acid and p-methoxyphenylacetylene as the hydroborated substrates, and (ii) for cyanosilylation, with trimethylcyanosilane (TMSCN) as the cyanosilylating agent and benzaldehyde as the substrate. The mechanistic understanding thus gained has then been further exploited experimentally to bring hydroboration and cyanosilylation closer to experimental conditions in catalysis. These insights can potentially be expanded to the rapidly growing area of solvent-free and internal catalyst chemistry.

Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene

Hypersilyl substituent in heavier low-valent group 14 chemistry - Gour, Kritika; Bisai, Milan Kumar; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2022)
The isolation of unusual compounds with low-valent main-group elements would not have been possible without the development of a series of sterically demanding ligands with bulky substituents. While early literature recognizes the advent of the sterically demanding tris(trimethylsilyl)silyl (SiMe3)(3)Si- group, also known as hypersilyl group, to stabilize species with new coordination modes for the main group elements, it has largely been more recent studies that have utilized this group for isolating stable compounds with low-valent main-group elements. Such compounds are not only interesting from the structure-bonding point of view but showcase potential for small molecule activation under ambient conditions. This review will cover the recent developments in stabilizing unusual compounds with group 14 elements using the exceptionally strong sigma-donor properties and pronounced steric effects of the hypersilyl moiety, emphasizing their synthesis, structure, and reactivity.
Keywords: Germylenes; Hydroboration; Hypersilyl; silylenes; Stannylenes

Zwitterionic disilanylium from an unsymmetrical disilene - Bisai, Milan Kumar; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The reaction of PhC(NtBu)2SiSi(SiMe3)(3) (1) with Me3SiCH(2)Cl afforded an unsymmetrical sp(2)-sp(3) disilene, 2, with concomitant elimination of Me3SiCl. The analogous reaction with PhC(NtBu)2SiCl resulted in the oxidative addition of the C-Cl bond at the Si(II) atom (3). The reactions of 2 with sulfur and selenium led to compounds with Si=E (E=S (4) and Se (5)) double bonds. Tellurium reacted differently with 2 and furnished a zwitterionic compound, 6.

Hypersilylsilylene-supported Ni(0) toluene and Ni(II) complexes with catalytic application - Ajithkumar, V. S.; Bisai, Milan Kumar; Ghanwat, Pratiksha B.; Raj, K. Vipin; Singh, Geetika; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2025)
The reaction of Ni(COD)2 with [PhC(NtBu)2SiSi(SiMe3)3] (1) in toluene results in the formation of an 18-electron silylene-Ni(0) toluene complex (2). The analogous reaction with 1,3-DFB instead of toluene affords the C-H activation followed by ring walking leading to the allylic cyclooctene adduct, the (eta 3-C8H13)Ni(II) complex (3). DFT calculations were carried out to elucidate the mechanism as well as to gain insight into why 1,3-DFB undergoes C-H bond activation instead of C-F bond activation. The use of NiCl2DME permits access to 16-electron (tetrylene)2NiCl2 (Si(4) and Ge(5)) species, and 4 was later used as a catalyst for the C-N coupling reaction.

Sila[1]ferrocenophanes with Bulky Substituents - Ajithkumar, V. S.; Bisai, Milan Kumar; Yuvaraj, K.; Gonnade, Rajesh G.; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
In this study, sila[1]ferrocenophanes with sterically bulky groups such as tris(trimethylsilyl) or N-heterocyclic iminato located at the bridging silicon atom are synthesized. The reactions of silicon-bound chloride in Fe(eta 5-C5H4)2SiCl2 (1) with K[Si(SiMe3)3] and silylated N-heterocyclic imine result in sila[1]ferrocenophanes 2 and 3 with bulky silicon- and nitrogen-based substituents at the ansa-bridge via elimination of KCl and Me3SiCl. Subsequently, the reduction of 1 is attempted using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (popularly known as Mashima reagent), which leads to the elimination of Me3SiCl and generation of 1,4-dihydropyrazine-spanned sila[1]ferrocenophanes (4). All the compounds are structurally characterized.
Keywords: ansa-bridges; ferrocenophanes; hypersilyls; Mashima reagents; N-heterocyclic imines